Optimalisasi Pengolahan Nanas Khas Tangkit Jambi Berbasis Industri Halal oleh Kube Mega Buana Dalam Mendukung Ekonomi Syariah - Rafiqi, Rafiqi; Ridhwan, Ridhwan; Pratiwi, Heni; Pratama, Aditya; Zaini Aprizal, Yusuf; Roihan, Muhammad; Dean Amri, Ary; Saputra, Rivo (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
Tangkit Jambi's distinctive pineapples have great potential as raw materials for value-added processed products. However, limitations in processing technology and business management in accordance with halal principles hinder the development of these products. This proposal aims to optimize halal-based pineapple processing through the empowerment of KUBE Mega Buana, with training in processing, halal certification, and marketing of halal products. The targeted outcomes are high-quality halal pineapple processed products, KUBE members who are competent in sharia business management, and the formation of a halal MSME ecosystem in Tangkit. This activity supports the development of a fair, sustainable, and empowering sharia economy for the local community.